Ecological Acoustics Perspective for Content-Based Retrieval of Environmental Sounds. (5th December 2010) - Roma, Gerard; Janer, Jordi; Kersten, Stefan; Schirosa, Mattia; Herrera, Perfecto; Serra, Xavier
Abstract : In this paper we present a method to search for environmental sounds in large unstructured databases of user-submitted audio, using a general sound events taxonomy from ecological acoustics. We discuss the use of Support Vector Machines to classify sound recordings according to the taxonomy and describe two use cases for the obtained classification models: a content-based web search interface for a large audio database and a method for segmenting field recordings to assist sound design.